Immunotherapy for the Treatment of Cutaneous Squamous Cell Carcinoma - Boutros, Andrea; Cecchi, Federica; Tanda, Enrica Teresa; Croce, Elena; Gili, Riccardo; Arecco, Luca; Spagnolo, Francesco; Queirolo, Paola (Frontiers in Oncology, 2021)
Cutaneous squamous cell carcinoma (CSCC) accounts for approximately 20% of all keratinocytic tumors. In most cases, the diagnosis and treatments are made on small, low-risk lesions. However, in about 5% of cases, CSCC may present as either locally advanced or metastatic (i.e. with locoregional lymph nodes metastases or distant localizations). Prior to the introduction of immunotherapy in clinical practice, the standard treatment of advanced CSCC was not clearly defined, and up to 60% of patients received no systemic therapy. Thanks to a strong pre-clinical rationale, clinical trials led to the FDA (Food and Drug Administration) and EMA (European Medicines Agency) registration of cemiplimab, a PD-1 inhibitor that achieved encouraging results in terms of objective response, overall survival, and quality of life. Subsequently, the anti-PD-1 pembrolizumab received the approval for the treatment of advanced CSCC by the FDA only. In this review, we will focus on the definition of advanced CSCC and on the current and future therapeutic options, with a particular regard for immunotherapy.